Preliminary studies on phytochemicals and cytotoxic activity of methanolic rhizome extract of Hedychium coronarium - Dash, Pritesh Ranjan; Sheikh, Zara (© 2015 Journal of Pharmacognosy and Phytochemistry, 2016)
This article was published in the Journal of Pharmacognosy and Phytochemistry [©2015 Journal of Pharmacognosy and Phytochemistry] The definite version is available at: https://goo.gl/aChrRS